A dietary pattern based on estrogen metabolism is associated with breast cancer risk in a prospective cohort of postmenopausal women. Issue 3 (6th April 2018) - Guinter, Mark A.; McLain, Alexander C.; Merchant, Anwar T.; Sandler, Dale P.; Steck, Susan E.
Abstract : Increased exposure to estrogen is a risk factor for postmenopausal breast cancer, and dietary factors can influence estrogen metabolism. However, studies of diet and breast cancer have been inconclusive. We developed a dietary pattern associated with levels of unconjugated estradiol and the ratio of 2‐ and 16‐hydroxylated estrogen metabolites in a subsample of Prostate, Lung, Colorectal and Ovarian Screening Trial (PLCO) participants ( n  = 653) using reduced rank regression, and examined its association with postmenopausal breast cancer prospectively in the larger PLCO cohort ( n  = 27, 488). The estrogen‐related dietary pattern (ERDP) was comprised of foods with positively‐weighted intakes (non‐whole/refined grains, tomatoes, cruciferous vegetables, cheese, fish/shellfish high in ω‐3 fatty acids, franks/luncheon meats) and negatively‐weighted intakes (nuts/seeds, other vegetables, fish/shellfish low in ω‐3 fatty acids, yogurt, coffee). A 1‐unit increase in the ERDP score was associated with an increase in total (HR: 1.09, 95% CI: 1.01–1.18), invasive (HR: 1.13; 95% CI: 1.04–1.24) and estrogen receptor (ER)‐positive (HR: 1.13, 95% CI: 1.02–1.24) breast cancer risk after adjustment for confounders. Associations were observed for the fourth quartile of ERDP compared with the first quartile for overall breast cancer (HR: 1.14; 95% CI: 0.98–1.32), invasive cases (HR: 1.20, 95% CI: 1.02–1.42) and ER‐positive cases (HR: 1.19; 95% CI: 0.99–1.41). The increased risk associated with increasing ERDP score was more apparent in strata of some effect modifiers (postmenopausal hormone therapy non‐users and non‐obese participants) where the relative estrogen exposure due to that factor was lowest, although the p values for interaction were not statistically significant. Results suggest a dietary pattern based on estrogen metabolism is positively associated with postmenopausal breast cancer risk, possibly through an estrogenic influence. Abstract : What's new? Serum levels of estrogen metabolites, which may be influenced by certain dietary factors, are associated with postmenopausal breast cancer risk. However, studies of diet and breast cancer have been inconclusive. In our study, an estrogen‐related dietary pattern (ERDP) was developed based on data from dietary questionnaires and serum concentrations of estrogen metabolites in a subsample of control participants and cancer patients. The ERDP strongly correlated with the intake of refined grains, cheese, lunch meats and yogurt. The ERDP was positively associated with postmenopausal breast cancer risk, with stronger effects in invasive and estrogen receptor‐positive cases.